The race for AI hegemony - Victor Diogho Heuer de Carvalho (Socioeconomic Analytics)
The growing use of Artificial Intelligence (AI) raises technical, economic, social, legal, and ethical questions. AI can transform industries, automate tasks, and create jobs, but it also brings concerns about infrastructure, resource redistribution, inequality, regulation, and ethics. The race for AI Hegemony between the US and China intensifies economic and political polarization. Investments in research and development will be massive, with competition for talent and resources. Without international coordination, the uncontrolled advance of AI could threaten security and social justice. An inclusive debate is essential to ensure the responsible use of this technology. This text was motivated by recent geopolitical events (already in the first month of 2025), which directly affect people's daily lives worldwide, leaving possible reflections on the power of AI as an active agent in shaping the future of humanity.